Evaluación de contaminantes del polvo sedimentable en el centro de la ciudad de Loja. - Gaona Quevedo, Yosselyn Arianna (2019)
Air pollution is one of the biggest environmental problems facing today, mainly due to urban development. The present study considered the analysis of the presence and concentration of lead and cadmium in 24 sedimentary dust collection filters, previously obtained and corresponding to the downtown area of the city of Loja Av. Manuel Agustín Aguirre and Av. Universitaria, from the street Cristobal Colón to Alonso de Mercadillo street. The research used the methods developed by the EPA IO-3.1 compendium method for the selection, preparation and extraction of the filter material; the 3051 method used for microwave-assisted acid digestion of sediments, sludges, soils and oils and the IO-3.2 method used for the determination of metals in particle absorption spectrometry, to determine the relationship between climatic factors and the concentration of Pb and Cd, Pearson's linear correlation was applied using the Minitab program. The results of the concentration of Cd yielded values below the detection limits (˂0.001) so that this metal could not be determined. The highest values of Pb in the sediments were those found in the samples with code P45 / 11A corresponding to the stretch of Miguel Riofrío Street until Azuay Street with a concentration of 20.18 mg / kg and the sample P43 / 22J that belongs to the month of May and the section that goes from Vicente Rocafuerte street to Miguel Riofrío street with a concentration of 18.57 mg / kg, despite being the highest concentrations found in the concentration analysis, they are still below the permissible limits in sediments, with the exception of the permissible limit range set by the oceanographic and atmospheric administration of the United States NOAA that proposes a range of between 4 mg / kg to 17 mg / kg. In the country there is no regulation that establishes the permissible limits of metals in sediments, therefore, it was necessary to apply international standards of permissible limits of metals is sediments. The present study was able to establish the existence of contamination problems, having been able to determine the presence of lead in accumulated sediments on leaves of plants located in the study area that corresponds to the downtown area of the city of Loja. Keywords: Air pollution, sediments, Lead, Cadmium.